2018
DOI: 10.1007/s11676-018-0710-x
|View full text |Cite
|
Sign up to set email alerts
|

Snow damages on trees of an uneven age in mixed broadleaf forests: effects of topographical conditions and tree characteristics

Abstract: Snow damage on natural stands is an important problem concerning mountainous forest management. In the present research, the frequency and intensity of heavy snow damage on natural stands and the relationship of damages with characteristics of trees, stand and topography were studied in mountainous forests of northern Iran. A systematic sampling design was applied to the study area (140 ha), with 122 circular plots. The grid dimension was 100 m and each plot area was 1000 m 2 . The four types of snow damage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…stand was undamaged (0%). In an another research [9], the frequency and intensity of heavy snow damage on natural stands and the relationship of damages with the characteristics of trees, stand, and topography were studied in mountainous forests of northern Iran, and the frequency of snow-damaged trees was reported to be 18%, which included the following types: crown damage (8.6%), stem breakage (5.4%), uprooting (3.2%), and bending (1.4%). In another similar study [21], snow damage to trees in the mountain forests of northern Iran was reported to be 28%, with the following types of damage: uprooting (3%), trunk fracture (4%), crown fracture (10%), and bending (11%).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…stand was undamaged (0%). In an another research [9], the frequency and intensity of heavy snow damage on natural stands and the relationship of damages with the characteristics of trees, stand, and topography were studied in mountainous forests of northern Iran, and the frequency of snow-damaged trees was reported to be 18%, which included the following types: crown damage (8.6%), stem breakage (5.4%), uprooting (3.2%), and bending (1.4%). In another similar study [21], snow damage to trees in the mountain forests of northern Iran was reported to be 28%, with the following types of damage: uprooting (3%), trunk fracture (4%), crown fracture (10%), and bending (11%).…”
Section: Introductionmentioning
confidence: 91%
“…Cracking of trees bole and drying of branches were observed in young trees due to frost, but in accordance with the aim of this study, authors focused only on mechanical damage of snow and wind to trees. Snow and wind damage to trees was recorded in four types: branch breakage (i.e., broken crown branch >10%), bending (i.e., leaning or lying), stem breakage (i.e., broken tree main stem), and uprooting (fallen trees or trees with the majority of their roots out of the soil) [9,25,26]. Trees without the described damage were noted as undamaged.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Snowfall may prevalently induce breakage of crown branches [65] producing fallen DW. In the Hyrcanian forest, Tavankar et al [66] observed crown damage in the larger diameter trees, particularly in Alnus subcordata at the higher elevations, adding that Fagus orientalis was less affected.…”
Section: Deadwoodmentioning
confidence: 99%
“…Thus, the ratio between the photosynthetic ability of the tree (the crown as a source) and the size of the tissue respiration (the whole tree as a sink) is decreasing. As a result, the secondary growth (being a lower priority in carbon allocation) is affected, and trees become slender (tall but thin stems) and more susceptible to abiotic disturbances such as wind and snow [7,11,[18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%